Microdeformation measurement of concrete roadway slabs using fiber Bragg gratings (2010)
This paper presents a non-invasive method for measuring microdeformations in concrete structures using Bragg network sensors in optical fibers adhered to its surface. Measurements are made in concrete road slabs under a static load of 10 kN, finding an approximate ratio of 2: 1 between the deformation recorded by the sensors and the values thrown by a computational simulation with the finite element method. The use of these sensors is proposed for the structural monitoring of slabs in a road mesh with sensors distributed and multiplexed by wavelength. This is the first report in Colombia of measurement of deformation of road slabs using fiber optic sensors.